Providing environmental enrichments can reduce subclinical spondylolisthesis prevalence without affecting performance in broiler chickens - Da Silva, Marconi Italo Lourenço [UNESP]; De Lima Almeida Paz, Ibiara Correia [UNESP]; Jacinto, Andressa Silva [UNESP]; Filho, Marcos Antonio Nascimento [UNESP]; De Oliveira, Ana Beatriz Santos [UNESP]; Dos Santos, Ingrid Grazieli Althman [UNESP]; Dos Santos Mota, Francine [UNESP]; Caldara, Fabiana Ribeiro; Jacobs, Leonie (Public Library of Science (PLoS), 2023)
Environmental enrichment can increase the occurrence of natural behavior and improve leg health and other animal welfare outcomes in broiler chickens. This study aimed to assess the effects of three environmental enrichments, specifically hay bales, step platforms, and laser lights, on subclinical spondylolisthesis prevalence, productivity, behavior, and gait of broiler chickens (Gallus gallus domesticus). Twenty-four hundred day-old male Ross® AP95 chicks from a commercial hatchery were used in a completely randomized design with four treatments and four replicate pens per treatment. Pens contained either a Control (C) treatment, an environment similar to a commercial broiler chicken system without environmental enrichments, or an environment with either additional hay bales (HB), additional step platforms (SP), or additional laser lights (LL). Performance, yield, behavior (frequencies), gait score, and subclinical spondylolisthesis prevalences were assessed. When raised with SP or LL access, fewer chickens had subclinical spondylolisthesis than chickens without enrichments (C) or with HB access. Chickens with access to SP exhibited higher wing yield and less abdominal fat than animals from the C group. Chickens from the LL and HB treatments explored more and rested less frequently than animals from the C and SP treatments. As chickens aged, they became less active, exploring less and increasing resting and comfort behaviors. Treatments did not affect gait. Gait was not associated with subclinical spondylolisthesis prevalence. Environmental enrichments benefitted chicken health (subclinical spondylolisthesis) and behavior (exploration) without negative consequences for performance and yield. Copyright: